SEISMICITY RATE CHANGES IN ASSOCIATION WITH TIME DEPENDENT STRESS TRANSFER IN THE REGION OF NORTHERN AEGEAN SEA, GREECE - Leptokaropoulos, K. M.; Papadimitriou, E. E.; Orlecka–Sikora, B.; Karakostas, V. G. (Bulletin of the Geological Society of Greece, 2010)
The region of northern Aegean has suffered several strong earthquakes since the beginning of the 20th century, causing extensive damage and loss of lives. For the seismic hazard assessment in the area, several studies have been accomplished, among them being the ones dealing with the Coulomb stress changes due to the seismic slip caused by major earthquakes, in addition with the constant tectonic loading on the major regional faults. The aim of the present study is to evaluate if seismicity rate changes from 1964 to 2008 are associated with changes in the stress field. For this purpose the stronger events (Μw>5.8) that occurred in this period were considered and their contribution to the stress field evolution was investigated by calculations performed just before and after their occurrence. This influence was then examined in connection with the occurrence rate of small events (Μw > 3.8) for the respective time intervals. After defining the probability density function (PDF) of the small events distribution, a rate/state model was used to correlate static stress changes with seismicity rate and to compare the observed with the expected seismicity rate for each time period.